Development of Enterprise Architecture using a Framework with Agile Approach - Sandoval, Fanny; Galvez, Víctor; Moscoso, Oswaldo (Enfoque UTE, 2017)
The development of an enterprise architecture (EA) in large organizations is complex. Thus, is important that the implementation of EA creates value in early stages of the process. This document contains a proposal of an EA framework design with agile approach based in TOGAF. This proposal is done with the objective to streamline the EA process. This framework presents a new design taking into account the current regulations, the target line of the organization and the principles proposed by the agile approach of EA. The objectives of each phase of the architecture development method ADM of TOGAF are matched with the requirements of the organization to extract only those that are aligned to the business. The deliverables proposed by TOGAF are analyzed with the goal to obtain, integrate and reduce the documentation in the implementation and modeling phases. This reduction allows more flexibility, less impact in the processes, reduction in development time and costs.